Degradable antibacterial non-woven fabric and production method thereof
By filling the coated antibacterial gel in the hollow polypropylene fiber, combined with electron beam radiation and reduced pressure concentration treatment, the problem of insufficient antibacteriality and degradability of non-woven fabrics in the prior art is solved, and efficient inhibition is achieved bacteria, long-acting antibacterial and improving mechanical properties.
Patent Information
- Application Number
- CN202411563316.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The antibacteriality and degradability of the traditional Chinese medicine non-woven fabrics are insufficient, the antibacterial activity is easily affected, and biodegradable polymer materials have defects in thermal stability and mechanical properties.
Hollow polypropylene fibers are used as substrate and filled with a coated antibacterial gel made of luteolin microspheres, protein solutions and other monomers by specific preparation methods, combining electron beam radiation and Concentrate the treatment under reduced pressure to improve antibacterial durability and mechanical properties.
It realizes the efficient antibacterial and long-term antibacterial effects of non-woven fabrics, while improving the thermal stability and mechanical properties of the material, ensuring the durability and safety of the product during use.
Smart Images

Figure CN119465656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, and in particular to a degradable antibacterial nonwoven fabric and a production method thereof. Background Art
[0002] Non-woven fabric is a new type of material, which is characterized by the fact that there is no weaving process, but it is made by mixing, continuously and interweaving fibers or sheets through chemical, physical or mechanical methods. Due to its excellent properties such as softness, breathability, waterproofness, anti-static and anti-bacterial, it is widely used in various industries.
[0003] Non-woven fabrics are widely used in the field of medical and health care, and their main uses are: 1. Medical masks. Non-woven fabrics have excellent filtering effects in the production of masks. They can not only prevent particulate matter from entering, but also have strong durability and can effectively prevent the spread of viruses and bacteria. 2. Medical dressings. Non-woven fabrics have good air permeability and strong water absorption, which can effectively prevent the growth of bacteria after infection or trauma. 3. Medical gloves. Non-woven gloves have good epidemic prevention effects and can effectively isolate the spread of viruses and bacteria, and prevent medical staff from contacting patients' blood and secretions. It has also been widely used in the field of home life, and its main uses are: 4. Clothing fabrics: Non-woven fabrics have good air permeability, are soft and comfortable, and are not easy to pilling and pilling. They can be used to make underwear, underwear and other close-fitting clothing. 5. Furniture products. Non-woven fabrics have excellent waterproof, moisture-proof and anti-static properties, and can be used to make furniture products such as sofa cushions and mattresses. 6. Cleaning supplies. Non-woven fabrics have the characteristics of strong water absorption and easy cleaning, and can be used to make wiping cloths and rags. It also has many applications in the industrial field, and its main uses are: 7. Filter materials. Non-woven fabrics can be used to make filters for liquid and gas filtration through different materials and structural designs. 8. Packaging materials. Non-woven fabrics are waterproof and friction-resistant, and can be used to make packaging materials for industrial products. 9. Building materials. Non-woven fabrics have waterproof and anti-corrosion properties and can be used to make building materials, such as ground membrane waterproofing rolls.
[0004] The antibacterial properties and biodegradability of non-woven fabrics for medical masks, dressings and gloves in the prior art are usually achieved through some antibacterial agents and biodegradable polymer materials. However, the activity of the antibacterial agents is easily affected during the preparation process, thereby affecting the antibacterial properties of the final product. Although biodegradable polymer materials have good biodegradability, they have certain defects in thermal stability and mechanical properties.
[0005] In order to solve the above problems, the present invention decides to propose a degradable antibacterial non-woven fabric and production method technology for further optimization and improvement. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a degradable antibacterial non-woven fabric and a production method.
[0007] The technical scheme of the present invention is: a degradable antibacterial non-woven fabric, which comprises, by mass percentage, 8-15% of aliphatic polyester, 5-12% of coated antibacterial gel, 3-5% of PE fiber, 0.2-0.5% of antistatic agent and the remainder of hollow polypropylene fiber; the hollow polypropylene fiber is made by mixing molten polypropylene and polylactic acid in a mass ratio of 1:0.5-0.8, stretching for 15-25 minutes at a temperature of 200-250°C and a stretching multiple of 3-5 times, and then shaping at 100-150°C for 10-50 seconds.
[0008] Description: Although the degradable antibacterial non-woven fabrics in the prior art also have degradation effects and antibacterial properties, the activity of the antibacterial agent is easily affected during the preparation process, thereby affecting the antibacterial properties of the final product. Although the biodegradable polymer material has good degradability, it has certain defects in thermal stability and mechanical properties. The hollow structure of polypropylene fiber gives it a very high porosity, which effectively hinders and reduces heat conduction, and significantly improves thermal stability. The coated antibacterial gel can slow down the problem of the gel gradually weakening due to washing, friction or long-term exposure to the environment, thereby further improving the antibacterial durability.
[0009] Furthermore, the preparation method of the coated antibacterial gel is:
[0010] Step 1: Mix 80-90 wt % ethanol solution and zein in a mass ratio of 7-8:2-3 and stir until dissolved evenly to obtain a protein solution;
[0011] Step 2, controlling the stirring rate to 100-200 r / min, adding luteolin microspheres to the protein solution in a volume ratio of 1:3-5 under stirring, performing electron beam radiation treatment after the addition, and continuing to stir until uniform to obtain a mixture, adding acrylic acid monomer to the mixed solution at a mass ratio of 1:2-3 of the mixture: acrylic acid monomer under nitrogen protection, adjusting the reaction temperature to 35-50°C, reacting for 30-100 min, obtaining a reaction solution, and then controlling the stirring rate to 500-1000 r / min, adding the reaction solution to a composite solution of polyvinyl alcohol monomer and glutaraldehyde under stirring conditions, controlling the drop rate to 5-15 mL / min, and placing it for 1-2 hours, and then performing reduced pressure concentration and freeze drying to obtain a coated antibacterial gel; wherein the content of glutaraldehyde is 15-20 g / L, accounting for 5-8% of the mass of the polyvinyl alcohol monomer, and the mass ratio of the reaction solution to the composite solution is 1:2-3;
[0012] Description: Zein has good biocompatibility, biodegradability, and excellent film-forming and fiber-forming abilities. Forming a layer of protein film on the surface of luteolin microspheres and then wrapping them with hydrogel can protect the microspheres from enzyme degradation and prolong their circulation time in the body, thereby achieving a more lasting antibacterial effect. At the same time, the protein film can bind to the receptors on the bacterial cell wall by simulating the structure and function of bacterial surface molecules, thereby increasing the affinity between the microspheres and the bacterial cell wall, improving the targeting of the antibacterial agent, and improving the antibacterial effect. In addition, the structure and thickness of the protein solution at the above ratio are moderate, which will not hinder the effective diffusion of luteolin into the bacterial cells and reduce its antibacterial activity.
[0013] In practical applications, the antibacterial properties of medical masks, dressings and gloves may gradually weaken due to friction or long-term exposure to the environment. The protein molecules that can transfer energy to the surface of luteolin microspheres after electron beam irradiation in this application lead to the formation of new chemical bonds between protein chains, such as disulfide bonds, and increase the cross-linking density between protein molecules. This cross-linking effect can make the protein film more compact and stable, reduce its resistance to bacterial cell walls, and improve penetration efficiency. However, under low-dose irradiation, the tensile strength and elongation will drop sharply. Therefore, the subsequent reduced pressure concentration and freeze-drying can maintain the porous structure and biological activity of the hydrogel and utilize the porous structure to obtain the antibacterial effect of the microspheres. The structure can increase the specific surface area of the hydrogel, thereby increasing its chance of contact with microorganisms, helping to release antibacterial agents more effectively, and reducing the influence of electron beam radiation on the mechanical properties of the coated antibacterial gel while enhancing the antibacterial effect. Encapsulating luteolin microspheres in the hydrogel can control its release rate and improve its antibacterial effect. Luteolin has antioxidant, antibacterial, and antiviral physiological activities, which can denature microbial cell proteins and hinder energy synthesis. It is safe and non-toxic, has good biocompatibility, and can maintain high antibacterial properties after being exposed to the environment for 3 months. This shows that the non-woven fabric modified with the coated antibacterial gel has good antibacterial persistence.
[0014] Furthermore, the parameters of the reduced pressure concentration are: vacuum degree of -0.08 to -0.1 MPa, temperature of 60 to 70°C, and concentration to 15 to 30% of its original volume; the freeze-drying method is: pre-freezing, placing the concentrated product in a vacuum freeze dryer, lowering the temperature of the concentrated product to -60 to -40°C, and maintaining it for 3 to 5 hours;
[0015] Vacuum drying, when the temperature in the cold trap is reduced to -70 to -50°C, the vacuum degree is maintained at 20 to 30Pa, and vacuuming is started for sublimation drying, and the temperature in the drying chamber is increased to 30 to 50°C at a rate of 5 to 15°C / min, and the vacuum degree reaches 1 to 10Pa, and the drying is terminated to obtain a coated antibacterial gel;
[0016] Description: A lower vacuum degree helps to reduce the thermal decomposition of heat-sensitive components, thereby maintaining the stability and activity of the antibacterial agent in the gel. The appropriate temperature can promote the diffusion and coating of the effective ingredients in the gel, and improve the gel's penetration and killing ability of microorganisms. Temperature control can also ensure that the water in the gel evaporates at a lower boiling point, reducing thermal damage to the gel structure and components. Appropriate concentration can prevent the gel from excessive shrinkage or rupture, ensuring its performance in practical applications; the pre-freezing temperature is set between -40°C and -60°C to quickly form sufficiently small ice crystals while reducing damage to the product structure. The appropriate heating rate can optimize the drying process, making it easier to remove water from the sample, while reducing energy consumption and improving overall drying efficiency.
[0017] Furthermore, the electron beam irradiation parameters are: irradiation reaction temperature is 50-60° C., irradiation time is 60-90 min, and irradiation intensity is 200-400 kGy.
[0018] Note: The above radiation parameters are appropriate and can effectively reduce the obstruction of the protein film to the bacterial cell wall and improve its penetration efficiency, while also protecting the tensile strength of the coated antibacterial gel.
[0019] Furthermore, the luteolin microspheres are spherical three-dimensional network structures obtained by reverse suspension polymerization of luteolin, water-soluble monomers and cross-linking agents in a mass ratio of 10:100-200:11-21;
[0020] Description: The application of spherical three-dimensional network structure in coated antibacterial gel can significantly improve the antibacterial durability and effect of antibacterial gel. This structure can provide a larger specific surface area, allowing the antibacterial agent to be more evenly distributed in the gel network, thereby increasing the contact opportunity with microorganisms and antibacterial efficiency. In addition, the spherical three-dimensional network structure can also limit the movement and diffusion of bacteria, reduce the ability of bacteria to resist antibacterial agents, and further enhance the antibacterial activity of the gel.
[0021] Furthermore, the water-soluble monomer is at least one of acrylic acid, methacrylic acid, and acrylamide, and the cross-linking agent is dimethylacrylamide or ethylene glycol dimethacrylate;
[0022] Description: Acrylic acid and methacrylic acid contain carboxyl groups, which can provide good water solubility and hydrophilicity, and help improve the wettability and hydrophilicity of non-woven fabrics. Acrylamide, because it contains amide groups, can form a polymer network with high mechanical strength and wear resistance after polymerization. The water-soluble polymers formed by copolymerization of these monomers can be used as adhesives to significantly improve the strength and durability of non-woven fabrics. The polymer network structure can form a more stable three-dimensional network through dimethylacrylamide or ethylene glycol dimethacrylate, thereby improving thermal stability and chemical stability, increasing the rigidity and tensile strength of the material, and improving its mechanical properties. In addition, the above-mentioned cross-linking agents can adjust the release rate of drugs for polymers containing drugs or active ingredients to achieve controlled release or sustained release effects.
[0023] Further, the aliphatic polyester is poly(ε-caprolactone) or polybutylene succinate / adipate, and the antistatic agent is NW16 antistatic agent;
[0024] Description: Poly(ε-caprolactone) will form ε-caproic acid and ethylene glycol when degraded. These degradation products can be further utilized by microorganisms in the environment, thereby achieving biodegradation; in the natural environment, polybutylene succinate / adipate can be decomposed by microorganisms and eventually converted into carbon dioxide and water.
[0025] The present invention also provides a method for preparing a degradable antibacterial non-woven fabric, comprising the following steps:
[0026] S1. Pretreatment of hollow polypropylene fibers
[0027] The hollow polypropylene fiber was treated with plasma at a working pressure of 35-45 Pa and a discharge power of 85-95 W for 4-7 minutes to obtain a clean and intact hollow polypropylene fiber.
[0028] S2. Filling of coated antibacterial gel
[0029] Then, the hollow polypropylene fiber is placed in a closed container, and air is pumped out by a vacuum pump until the pressure of the closed container is 4-6 MPa. The coated antibacterial gel is filled into the hollow polypropylene fiber by an injection device to obtain a non-woven fabric matrix; the injection pressure is 0.1-0.3 MPa, the injection speed is 100-200 mg / s, and the filling amount of the coated antibacterial gel accounts for 90-95% of the volume of the hollow part of the hollow polypropylene fiber;
[0030] S3, Roller Pressing
[0031] The aliphatic polyester, PE fiber and antistatic agent are melt-mixed at 180-220° C. to obtain a molten mixture, and then the molten mixture is coated on the surface of the non-woven fabric substrate with a coating thickness of 0.3-0.5 μm, and then rolled for 20-30 minutes at a roller speed of 0.1-6 m / min and a roller gap of 0.5-3 mm to obtain a non-woven fabric;
[0032] S4. Finalization
[0033] The non-woven fabric obtained in step S3 is cured to obtain a degradable antibacterial non-woven fabric.
[0034] Description: Plasma treatment can change the surface energy of polypropylene fibers and introduce polar groups, thereby improving the wettability and bonding properties of the fibers. These parameters can ensure the best effect of plasma treatment while avoiding excessive damage to the fibers. Injecting gel into polypropylene fibers under low pressure helps the gel enter the tiny gaps in the hollow structure, thereby improving its antibacterial durability and antibacterial effect.
[0035] Further, in step S4, the curing temperature is 25 to 35° C., and the curing time is 15 to 30 min;
[0036] Note: The above curing temperature can promote the arrangement of the internal molecular chains of the non-woven fabric, making the arrangement more compact and reducing the gaps between molecules, thereby enhancing the thermal stability of the non-woven fabric. Moderate curing parameters also help maintain a certain flexibility, making the non-woven fabric more comfortable and durable in use.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present application introduces luteolin into the coated antibacterial gel and makes luteolin into microspheres and further encapsulates them in hydrogel, so as to achieve slow and sustained release of luteolin, which is then filled into hollow polypropylene fibers to enable the polypropylene fibers to have good thermal stability and long-lasting antibacterial effect. Luteolin is a natural plant-derived compound with significant antibacterial activity. The coated antibacterial gel can protect luteolin from rapid degradation while ensuring that it maintains an effective concentration in the application area to combat bacterial growth and reproduction. At the same time, the sustained release of luteolin can also promote the healing of chronic wounds.
[0039] (2) The present application adds protein solution treatment in the process of preparing the coated antibacterial gel. By forming a layer of protein film on the surface of the luteolin microspheres and then wrapping them with hydrogel, the microspheres can be protected from enzyme degradation, thereby further optimizing the antibacterial durability of the coated antibacterial gel. The protein film is used to simulate the structure and function of bacterial surface molecules to increase the affinity of the microspheres to the bacterial cell wall, improve the targeting of the antibacterial agent, and improve the antibacterial effect. Then, electron beam irradiation is used to increase the cross-linking density between protein molecules, reduce their obstruction to the bacterial cell wall, and improve the penetration efficiency.
[0040] (3) The present application adds the steps of reduced pressure concentration and freeze drying in the process of preparing the coated antibacterial gel, which can more effectively release the antibacterial agent while maintaining the porous structure and biological activity of the hydrogel, and can also weaken the influence of electron beam radiation on the mechanical properties of the coated antibacterial gel while enhancing the antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a schematic diagram of a spherical three-dimensional network structure according to Embodiment 1 of the present invention;
[0042] Figure 2 It is a comparison chart of the breaking strength performance of the degradable antibacterial non-woven fabrics of Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;
[0043] Figure 3 It is a comparison chart of thermal stability of the degradable antibacterial nonwoven fabrics of Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;
[0044] Figure 4 It is a comparison chart of the antibacterial strength and antibacterial durability of the degradable antibacterial non-woven fabrics of Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;
[0045] Figure 5 It is a comparison chart of the breaking strength performance of the degradable antibacterial non-woven fabrics of Example 1, Example 6 to Example 17 and Comparative Examples 3 to Comparative Examples 6 of the present invention;
[0046] Figure 6 It is a comparison chart of thermal stability of the degradable antibacterial nonwoven fabrics of Example 1, Example 6 to Example 17 and Comparative Examples 3 to Comparative Examples 6 of the present invention;
[0047] Figure 7 It is a comparison chart of the antibacterial strength and antibacterial durability of the degradable antibacterial non-woven fabrics of Example 1, Example 6 to Example 17 and Comparative Examples 3 to Comparative Examples 6 of the present invention;
[0048] Figure 8It is a comparison chart of the breaking strength performance of the degradable antibacterial nonwoven fabrics of Example 1, Examples 18 to 25 and Comparative Example 7 of the present invention;
[0049] Fig. 9 It is a comparison chart of thermal stability of the degradable antibacterial nonwoven fabrics of Example 1, Examples 18 to 25 and Comparative Example 7 of the present invention;
[0050] Fig.10 It is a comparison chart of the antibacterial strength and antibacterial durability of the degradable antibacterial non-woven fabrics of Example 1, Examples 18 to 25 and Comparative Example 7 of the present invention. DETAILED DESCRIPTION
[0051] In order to further illustrate the method and effect of the present invention, the technical solution of the present invention will be clearly and completely described in combination with experiments.
[0052] Embodiment 1: A degradable antibacterial nonwoven fabric comprises, by mass percentage, 12% aliphatic polyester, 7% coated antibacterial gel, 4% PE fiber, 0.4% antistatic agent and the remainder hollow polypropylene fiber; the hollow polypropylene fiber is prepared by mixing molten polypropylene and polylactic acid in a mass ratio of 1:0.7, stretching for 20 minutes at a temperature of 225°C and a stretching multiple of 4 times, and then setting at 125°C for 30 seconds; the aliphatic polyester is poly(ε-caprolactone), and the antistatic agent is a commercially available NW16 antistatic agent;
[0053] The preparation method of the coated antibacterial gel is as follows:
[0054] Step 1: Mix 85 wt % ethanol solution and zein at a mass ratio of 3:1 and stir until they are uniformly dissolved to obtain a protein solution; wherein the zein is a commercially available product;
[0055] Step 2, controlling the stirring rate to 150r / min, adding luteolin microspheres to the protein solution in a volume ratio of 1:4 under stirring, performing electron beam irradiation treatment after the addition, and continuing to stir until uniform to obtain a mixture, adding acrylic acid monomer to the mixed solution at a mass ratio of 1:2.5 of the mixture: acrylic acid monomer under nitrogen protection, adjusting the reaction temperature to 35-50°C, reacting for 30-100min, obtaining a reaction solution, and then controlling the stirring rate to 800r / min, adding the reaction solution to a composite solution of polyvinyl alcohol monomer and glutaraldehyde under stirring conditions, controlling the drop rate to 10mL / min, and placing it for 1.5h, and then performing reduced pressure concentration and freeze-drying treatment to obtain a coated antibacterial gel; wherein the content of glutaraldehyde is 18g / L, accounting for 7% of the mass of the polyvinyl alcohol monomer, and the mass ratio of the reaction solution to the composite solution is 1:2.5;
[0056] The parameters of reduced pressure concentration are: vacuum degree of -0.09 MPa, temperature of 65°C, and concentration to 22% of its original volume;
[0057] The freeze-drying treatment method is as follows: pre-freezing, placing the concentrated product in a vacuum freeze dryer, lowering the temperature of the concentrated product to -45°C, and maintaining it for 4 hours;
[0058] Vacuum drying, when the temperature in the cold trap is reduced to -60°C, the vacuum degree is maintained at 25Pa, and vacuuming is started for sublimation drying. The temperature in the drying chamber is increased to 40°C at a rate of 10°C / min and the vacuum degree reaches 6Pa, and the coated antibacterial gel is obtained;
[0059] The electron beam irradiation parameters were as follows: irradiation reaction temperature was 55 °C, irradiation time was 75 min, and irradiation intensity was 300 kGy;
[0060] Luteolin microspheres are spherical three-dimensional network structures obtained by reverse suspension polymerization of luteolin, water-soluble monomers and cross-linking agents in a mass ratio of 2:30:3. The cross-linking agent is dimethyl acrylamide. Figure 1 As shown;
[0061] The water-soluble monomer is acrylic acid;
[0062] A method for preparing a degradable antibacterial nonwoven fabric comprises the following steps:
[0063] S1. Pretreatment of hollow polypropylene fibers
[0064] The hollow polypropylene fiber was treated with plasma at a working pressure of 40Pa and a discharge power of 90W for 5 minutes to obtain a clean and intact hollow polypropylene fiber.
[0065] S2. Filling of coated antibacterial gel
[0066] Then, the hollow polypropylene fiber is placed in a closed container, and the air is evacuated by a vacuum pump until the pressure of the closed container is 5 MPa. The coated antibacterial gel is filled into the hollow polypropylene fiber by an injection device to obtain a non-woven fabric matrix; the injection pressure is 0.2 MPa, the injection speed is 150 mg / s, and the filling amount of the coated antibacterial gel accounts for 93% of the volume of the hollow part of the hollow polypropylene fiber;
[0067] S3, Roller Pressing
[0068] The aliphatic polyester, PE fiber and antistatic agent are melt-mixed at 200° C. to obtain a molten mixture, and then the molten mixture is coated on the surface of the non-woven fabric substrate with a coating thickness of 0.3 to 0.5 μm, and then rolled for 25 minutes at a roller speed of 3 m / min and a roller gap of 1.5 mm to obtain a non-woven fabric;
[0069] S4. Finalization
[0070] The non-woven fabric obtained in step S3 is cured to obtain a degradable antibacterial non-woven fabric; the curing temperature is 30° C. and the curing time is 25 min.
[0071] Example 2: Different from Example 1, a degradable antibacterial non-woven fabric comprises, by mass percentage, 8% aliphatic polyester, 5% coated antibacterial gel, 3% PE fiber, 0.2% antistatic agent and the remainder hollow polypropylene fiber.
[0072] Example 3: Different from Example 1, a degradable antibacterial non-woven fabric comprises, by mass percentage, 15% aliphatic polyester, 12% coated antibacterial gel, 5% PE fiber, 0.5% antistatic agent and the remainder hollow polypropylene fiber.
[0073] Example 4: Different from Example 1, the hollow polypropylene fiber is made by mixing molten polypropylene and polylactic acid in a mass ratio of 1:0.5, stretching at a temperature of 200°C and a stretching ratio of 3 times for 15 minutes, and then shaping at 100°C for 10 seconds.
[0074] Example 5: Different from Example 1, the hollow polypropylene fiber is made by mixing molten polypropylene and polylactic acid in a mass ratio of 1:0.8, stretching at a temperature of 250°C and a stretching ratio of 5 times for 25 minutes, and then shaping at 150°C for 50 seconds.
[0075] Example 6: Different from Example 1, in step 1, 80 wt % ethanol solution and zein are mixed and stirred at a mass ratio of 7:3 until they are uniformly dissolved.
[0076] Example 7: Different from Example 1, in step 1, 90 wt % ethanol solution and zein are mixed and stirred at a mass ratio of 8:2 until they are uniformly dissolved.
[0077] Example 8: Different from Example 1, in step 2, the stirring rate is controlled to 100 r / min, and the luteolin microspheres are added to the protein solution in a volume ratio of 1:3 under stirring. After the addition, the solution is subjected to electron beam irradiation treatment and continued to be stirred until uniform to obtain a mixture. Under nitrogen protection, acrylic acid monomer is added to the mixed solution in a mass ratio of 1:2 of the mixture: acrylic acid monomer. The reaction temperature is adjusted to 35°C and the reaction is carried out for 30 minutes to obtain a reaction solution. The stirring rate is then controlled to 500 r / min, and the reaction solution is added to the composite solution of polyvinyl alcohol monomer and glutaraldehyde under stirring. The dropping rate is controlled to 5 mL / min. After standing for 1 hour, the solution is concentrated under reduced pressure and freeze-dried to obtain a coated antibacterial gel.
[0078] Example 9: Different from Example 1, in step 2, the stirring rate is controlled to 200 r / min, and the luteolin microspheres are added to the protein solution in a volume ratio of 1:5 under stirring. After the addition, the solution is subjected to electron beam irradiation treatment and continued to be stirred until uniform to obtain a mixture. Under nitrogen protection, acrylic acid monomer is added to the mixed solution in a mass ratio of 1:3 of the mixture: acrylic acid monomer. The reaction temperature is adjusted to 50°C and the reaction is carried out for 100 min to obtain a reaction solution. The stirring rate is then controlled to 1000 r / min, and the reaction solution is added to the composite solution of polyvinyl alcohol monomer and glutaraldehyde under stirring. The dropping rate is controlled to 15 mL / min. After standing for 2 hours, the solution is concentrated under reduced pressure and freeze-dried to obtain an encapsulated antibacterial gel.
[0079] Example 10: Different from Example 1, in step 2, the content of glutaraldehyde is 15 g / L, accounting for 5% of the mass of polyvinyl alcohol, and the mass ratio of the reaction solution to the composite solution is 1:2.
[0080] Example 11: Different from Example 1, in step 2, the content of glutaraldehyde is 20 g / L, accounting for 8% of the mass of polyvinyl alcohol, and the mass ratio of the reaction solution to the composite solution is 1:3.
[0081] Example 12: Different from Example 1, in step 2, the parameters of reduced pressure concentration are: vacuum degree of -0.08 MPa, temperature of 60°C, and concentration to 15% of its original volume;
[0082] The freeze-drying treatment method is as follows: pre-freezing, placing the concentrated product in a vacuum freeze dryer, lowering the temperature of the concentrated product to -40°C, and maintaining it for 5 hours;
[0083] Vacuum drying, when the temperature in the cold trap is reduced to -70°C, the vacuum degree is maintained at 20Pa, and vacuuming is started for sublimation drying. The temperature in the drying chamber is increased to 30°C at a rate of 5°C / min and the vacuum degree reaches 1Pa, and the coated antibacterial gel is obtained.
[0084] Example 13: Different from Example 1, in step 2, the parameters of reduced pressure concentration are: vacuum degree of -0.1 MPa, temperature of 70°C, and concentration to 30% of its original volume;
[0085] The freeze-drying treatment method is as follows: pre-freezing, placing the concentrated product in a vacuum freeze dryer, lowering the temperature of the concentrated product to -55°C, and maintaining it for 3 hours;
[0086] Vacuum drying, when the temperature in the cold trap is reduced to -50°C, the vacuum degree is maintained at 30Pa, and vacuuming is started for sublimation drying. The temperature in the drying chamber is increased to 50°C at a rate of 15°C / min and the vacuum degree reaches 10Pa, and the coated antibacterial gel is obtained.
[0087] Example 14: Different from Example 1, in step 2, the electron beam irradiation parameters are: irradiation reaction temperature is 50°C, irradiation time is 60min, and radiation intensity is 200kGy.
[0088] Example 15: Different from Example 1, in step 2, the electron beam irradiation parameters are: irradiation reaction temperature is 60°C, irradiation time is 90min, and radiation intensity is 400kGy.
[0089] Example 16: Different from Example 1, in step 2, the water-soluble monomer is methacrylic acid.
[0090] Example 17: Different from Example 1, in step 2, the water-soluble monomer is acrylamide.
[0091] Example 18: Different from Example 1, in step S1, the hollow polypropylene fiber is plasma treated for 4 minutes at a working pressure of 35 Pa and a discharge power of 85 W.
[0092] Example 19: Different from Example 1, in step S1, the hollow polypropylene fiber is plasma treated for 7 minutes at a working pressure of 45 Pa and a discharge power of 95 W.
[0093] Example 20: Different from Example 1, in step S2, the vacuum pump draws out air to a closed container with a pressure of 4 MPa, the injection pressure is 0.1 MPa, the injection speed is 100 mg / s, and the filling amount of the coated antibacterial gel accounts for 90-95% of the volume of the hollow part of the hollow polypropylene fiber.
[0094] Example 21: Different from Example 1, in step S2, the vacuum pump draws out air to a closed container with a pressure of 6 MPa, the injection pressure is 0.3 MPa, the injection speed is 200 mg / s, and the filling amount of the coated antibacterial gel accounts for 95% of the volume of the hollow part of the hollow polypropylene fiber.
[0095] Example 22: Different from Example 1, in step S3, the aliphatic polyester, PE fiber and antistatic agent are melt mixed at 180°C to obtain a molten mixture, and then the molten mixture is coated on the surface of the non-woven fabric substrate with a coating thickness of 0.3 μm, and then rolled for 20 minutes at a roller speed of 0.1 m / min and a roller gap set to 0.5 mm to obtain a non-woven fabric.
[0096] Example 23: Different from Example 1, in step S3, the aliphatic polyester, PE fiber and antistatic agent are melt mixed at 220°C to obtain a molten mixture, and then the molten mixture is coated on the surface of the non-woven fabric substrate with a coating thickness of 0.5 μm, and then rolled for 30 minutes at a roller speed of 6 m / min and a roller gap of 3 mm to obtain a non-woven fabric.
[0097] Example 24: Different from Example 1, in step S4, the curing temperature is 25°C and the curing time is 15 minutes.
[0098] Example 25: Different from Example 1, in step S4, the curing temperature is 35°C and the curing time is 30 minutes.
[0099] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0100] In order to explore the performance of the nonwoven fabrics manufactured in Examples 1 to 25 and Comparative Examples 1 to 7, each group was cut into 3 strips of 15 mm × 20 mm, and the mechanical properties were tested using an electronic tensile testing machine in accordance with GB / T24218-2017 "Test methods for textile nonwovens Part 3: Determination of breaking strength and breaking elongation (strip method)". The experimental results are as follows Figure 2 , Figure 5 , Figure 8 As shown; the test was carried out with reference to the standard GB / T21510-2008 "Test Method for Antibacterial Performance of Nano-inorganic Materials", and the antibacterial ability of the sample against Escherichia coli in the initial state was used as a reference. The sample was exposed to room temperature for 3 months and then its antibacterial ability against Escherichia coli was retested. The experimental results are shown as follows Figure 4 , Figure 7 , Fig.10 As shown; the sample was placed in an oven at 80°C for 4 hours, and the filtration efficiency of the non-woven fabric after heat aging for saline sodium chloride aerosol with a particle size of 0.3 μm was tested using a CSI-506A automatic filter material tester. Figure 3 , Figure 6 , Fig. 9 The experimental results are as follows:
[0101] 1. Explore the effects of various components on the performance of biodegradable antibacterial non-woven fabrics
[0102] Comparative Example 1: Different from Example 1, the polypropylene fiber does not adopt a hollow structure.
[0103] Comparative Example 2: Different from Example 1, no PE fiber is added.
[0104] Conclusion: Figures 2 to 4 From the comparison of Examples 1 to 3 and Comparative Example 1, it can be seen that the polypropylene fiber does not adopt a hollow structure, which significantly reduces the breaking strength, thermal stability and antibacterial effect and durability of the degradable antibacterial non-woven fabric. This is mainly because the hollow structure of the polypropylene fiber gives it a very high porosity, which effectively hinders and reduces heat conduction, thereby significantly improving the thermal stability. The coated antibacterial gel can slow down the problem of the gel gradually weakening due to washing, friction or long-term exposure to the environment, thereby further improving the antibacterial durability. From the comparison of Examples 1 to 3 and Comparative Example 2 in the figure, it can be seen that the addition of a small amount of PE fiber can improve the mechanical properties of the non-woven fabric, including the breaking strength.
[0105] 2. Investigate the effect of the preparation method of coated antibacterial gel on the performance of degradable antibacterial non-woven fabrics
[0106] Comparative Example 3: Different from Example 1, the luteolin microspheres were not treated with protein solution.
[0107] Comparative Example 4: Different from Example 1, no electron beam radiation treatment was performed.
[0108] Comparative Example 5: Different from Example 1, no reduced pressure concentration treatment was performed.
[0109] Comparative Example 6: Different from Example 1, the structure of the luteolin microspheres is not limited.
[0110] Conclusion: If Figures 5 to 7 As shown, by comparing Example 1, Examples 6 to 7 and Comparative Example 3, it can be seen that the antibacterial effect and antibacterial persistence of the degradable antibacterial non-woven fabric obtained in Comparative Example 3 without protein solution treatment showed a significant downward trend, which shows that first forming a layer of protein film on the surface of luteolin microspheres and then encapsulating them with hydrogel can protect the microspheres from enzyme degradation and prolong their circulation time in the body, thereby achieving a more lasting antibacterial effect. At the same time, the protein film can bind to the receptors on the bacterial cell wall by simulating the structure and function of the bacterial surface molecules, thereby increasing the affinity between the microspheres and the bacterial cell wall, improving the targeting of the antibacterial agent, and improving the antibacterial effect.
[0111] From the comparison of Example 1, Examples 8 to 9, and Comparative Examples 4 and 5, it can be seen that the performance of the degradable antibacterial non-woven fabrics obtained without electron radiation treatment in Comparative Examples 4 and 5 also showed a significant downward trend, wherein the electron beam irradiated protein molecules that can transfer energy to the surface of the luteolin microspheres, resulting in the formation of new chemical bonds between protein chains, such as disulfide bonds, increasing the cross-linking density between protein molecules, and this cross-linking effect can make the protein film more compact and stable, reduce its hindrance to the bacterial cell wall, and improve the penetration efficiency, but at the same time of irradiation, the tensile strength and elongation will drop sharply, that is, the situation of Comparative Example 5, so in the process of preparing the coated antibacterial gel, the electron radiation treatment and the reduced pressure concentration treatment are complementary effects;
[0112] From the comparison between Example 1 and Comparative Example 6, it can be seen that the conventional spherical structure used in Comparative Example 6 also causes the antibacterial performance of the degradable antibacterial non-woven fabric to show a significant downward trend. This is because the application of the spherical three-dimensional network structure in the coated antibacterial gel can significantly improve the antibacterial durability and effect of the antibacterial gel. This structure can provide a larger specific surface area, so that the antibacterial agent can be more evenly distributed in the gel network, thereby increasing the contact opportunity with microorganisms and the antibacterial efficiency. In addition, the spherical three-dimensional network structure can also limit the movement and diffusion of bacteria, reduce the ability of bacteria to resist antibacterial agents, and further enhance the antibacterial activity of the gel.
[0113] 3. Investigate the influence of preparation method on the performance of biodegradable antibacterial non-woven fabrics
[0114] Comparative Example 7: Different from Example 1, in step S3, no rolling process is performed.
[0115] Conclusion: If Figures 8 to 10 As shown, by comparing Example 1, Examples 22-23 and Comparative Example 7, it can be seen that the various properties of the degradable antibacterial non-woven fabric obtained without roller pressing in Comparative Example 7 are also weakened, which shows that the roller pressing process compresses the coated non-woven fabric by mechanical means to eliminate bubbles and enhance the bonding force between fibers, thereby improving the overall strength and flatness of the non-woven fabric. Rolling can also help the chemical substances to be more evenly distributed in the non-woven fabric and improve the consistency of its performance. In summary, Example 1 is the best solution.
Claims
1. A degradable antibacterial nonwoven fabric, characterized in that: According to the mass percentage, it includes: 8-15% aliphatic polyester, 5-12% coated antibacterial gel, 3-5% PE fiber, 0.2-0.5% antistatic agent and the rest hollow polypropylene fiber; the hollow polypropylene fiber is made by mixing molten polypropylene and polylactic acid in a mass ratio of 1:0.5-0.8, stretching for 15-25 minutes at a temperature of 200-250°C and a stretching multiple of 3-5 times, and then shaping at 100-150°C for 10-50 seconds.
2. A degradable antibacterial nonwoven fabric as claimed in claim 1, characterized in that: The preparation method of the coated antibacterial gel is: Step 1: Mix 80-90 wt % ethanol solution and zein in a mass ratio of 7-8:2-3 and stir until dissolved evenly to obtain a protein solution; Step 2, controlling the stirring rate to 100-200 r / min, adding luteolin microspheres to the protein solution in a volume ratio of 1:3-5 under stirring, performing electron beam radiation treatment after the addition, and continuing to stir until uniform to obtain a mixture, adding acrylic acid monomer to the mixed solution at a mass ratio of 1:2-3 of the mixture: acrylic acid monomer under nitrogen protection, adjusting the reaction temperature to 35-50°C, reacting for 30-100 minutes, obtaining a reaction solution, and then controlling the stirring rate to 500-1000 r / min, adding the reaction solution to a composite solution of polyvinyl alcohol monomer and glutaraldehyde under stirring conditions, controlling the drop rate to 5-15 mL / min, and placing it for 1-2 hours, and then performing reduced pressure concentration and freeze drying to obtain a coated antibacterial gel; wherein the content of glutaraldehyde in the composite solution is 15-20 g / L, accounting for 5-8% of the mass of the polyvinyl alcohol monomer, and the mass ratio of the reaction solution to the composite solution is 1:2-3.
3. A degradable antibacterial nonwoven fabric as claimed in claim 2, characterized in that: The parameters of the reduced pressure concentration are: vacuum degree of -0.08 to -0.1 MPa, temperature of 60 to 70° C., and concentration to 15 to 30% of the original volume.
4. A degradable antibacterial nonwoven fabric as claimed in claim 2, characterized in that: The parameters of electron beam radiation are as follows: radiation reaction temperature is 50-60°C, radiation time is 60-90min, and radiation intensity is 200-400kGy.
5. The degradable antibacterial nonwoven fabric according to claim 2, characterized in that: The luteolin microspheres are spherical three-dimensional network structures obtained by reverse suspension polymerization of luteolin, water-soluble monomers and cross-linking agents in a mass ratio of 10:100-200:11-21.
6. The degradable antibacterial nonwoven fabric according to claim 5, characterized in that: The water-soluble monomer is at least one of acrylic acid, methacrylic acid and acrylamide, and the cross-linking agent is dimethylacrylamide or ethylene glycol dimethacrylate.
7. The degradable antibacterial nonwoven fabric according to claim 1, characterized in that: The aliphatic polyester is poly(ε-caprolactone) or polybutylene succinate / adipate, and the antistatic agent is NW16 antistatic agent.
8. The method for preparing a degradable antibacterial nonwoven fabric according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Pretreatment of hollow polypropylene fibers The hollow polypropylene fiber was treated with plasma at a working pressure of 35-45 Pa and a discharge power of 85-95 W for 4-7 minutes to obtain a clean and intact hollow polypropylene fiber. S2. Filling of coated antibacterial gel Then, the hollow polypropylene fiber is placed in a closed container, and air is pumped out by a vacuum pump until the pressure of the closed container is 4-6 MPa. The coated antibacterial gel is filled into the hollow polypropylene fiber by an injection device to obtain a non-woven fabric matrix; the injection pressure is 0.1-0.3 MPa, the injection speed is 100-200 mg / s, and the filling amount of the coated antibacterial gel accounts for 90-95% of the volume of the hollow part of the hollow polypropylene fiber; S3, Roller Pressing The aliphatic polyester, PE fiber and antistatic agent are melt-mixed at 180-220° C. to obtain a molten mixture, and then the molten mixture is coated on the surface of the non-woven fabric substrate with a coating thickness of 0.3-0.5 μm, and then rolled for 20-30 minutes at a roller speed of 0.1-6 m / min and a roller gap of 0.5-3 mm to obtain a non-woven fabric; S4. Finalization The non-woven fabric obtained in step S3 is cured to obtain a degradable antibacterial non-woven fabric.
9. The method for producing a degradable antibacterial nonwoven fabric according to claim 8, characterized in that: In step S4, the curing temperature is 25-35° C., and the curing time is 15-30 minutes.